Perception of Undergraduate Students on the Natural History of the Human Being: A Case Study - Aponte, Héctor (2019)
The perception held by college students about the human evolution plays a crucial role in the understanding of our natural history. This study assessed, through an oral survey, the perception of college students on some aspects of our natural history (665 students from a private university in Metropolitan Lima, from both science and humanities study programs). The results obtained indicate that 50% of the population surveyed consider that a god did not take part in the evolutionary process, which reflects a position in accordance with non-theistic evolution, i.e., a clearly evolutionary materialistic position. Lower percentages accepted that the human being does not come from other animal species (20%) or that we lived at the same time as dinosaurs (23%). No differences were found between science and humanities students (p>.05), which indicates that the findings of this study are, most probably, a reflection of pre-school and school education. The results should be taken into account in the development of courses at the primary, secondary, and university levels so that these can include contents that reinforce the scientific conceptions of our natural history.